MONETARY AND FISCAL POLICY ANALYSIS: WHICH IS MORE EFFECTIVE? - Yunanto, Muhamad; Medyawati, Henny (Journal of Indonesian Economy and Business, 2014)
Fiscal policy is an adjustment in the income and expenditure of government as stipulated inthe state budget in order to achieve better economic stability and pace of development. Themain objective of this study was to measure and analyze Fiscal and Monetary Policy of theGross Domestic Product (GDP). Fiscal Policy Multiplier (FPM) and Monetary PolicyMultiplier (MPM) are used to answer the debate where more effective between fiscal policy andmonetary policy. Short-term models derived through error correction model (ECM), which alsoforms the derivative equation. A system of simultaneous equations two stage least squares(TSLS), is used to describe the sensitivity analysis (response) of shocks to the policy change ofimportant macroeconomic indicators. The results showed that during the study period,Indonesias monetary policy more effective than fiscal policy.Keywords: monetary policy, fiscal policy, Mundell-Flemming Model